Oxidation behavior of an ultra-high strength and ductile Ni-enriched complex concentrated alloy - Lakshay Chauhan; Sudeep Kumar T.; Arout Chelvane; Shanmugasundaram T. (Journal of Alloys and Metallurgical Systems)
Recent research work revealed that Ni43.9Co22.4Fe8.8Al10.7Ti11.7B2.5 HEA is one of the ultra-high strength and ductile superlattice alloys. In this work, high-temperature oxidation behavior of the as-cast Ni43.9Co22.4Fe8.8Al10.7Ti11.7B2.5 alloy was investigated at 1000 ℃ up to 100 h. The oxidized samples were characterized using X-ray Diffractometer, Energy Dispersive Spectroscopy, and X-ray Photoelectron Spectroscopy. The results revealed that the initial microstructure of the alloy consists of face centered cubic (FCC) and L12 structures. High-temperature exposure resulted in the formation of Al2O3 and TiO2 scales during the initial hours of oxidation, which eventually spall-off after 25 h of exposure allowing further oxidation. The results showed that protective oxide layers such as Al2O3 and TiO2 were not present after 100 h of exposure. The external layer of the 100 h oxidized sample was composed of Fe, Co, and Ni-rich oxides which are known to have mere effective resistance against oxygen ingression. The alloy which has superior strength and ductility may be used for high temperature applications after attaining the thermally stable fine-grain microstructure by suitable thermomechanical processing / providing oxidation resistance coating / by doping with elements having superior oxidation resistance.